EXISTENTIAL STRUGGLES AND EMBODIED FEMALE IDENTITY PORTRAYED IN MIEKO KAWAKAMI NOVEL BREASTS AND EGGS - Prihatina, Yoshinta Nur; Istiani, Imas (Esteem Journal of English Education Study Programme, 2025)
This study investigates the existential journeys of female characters in Breasts and Eggs by Mieko Kawakami, emphasizing the body as a site of identity formation amid cultural and societal constraints. Using a qualitative analytical approach grounded in existential feminist theory, the research uncovers the inner conflicts experienced by women as they confront issues of bodily autonomy, selfhood, and normative expectations. Through the experiences of Makiko, Natsuko, and Midoriko, the novel illustrates how ingrained cultural standards, reproductive expectations, and the internalization of objectification suppress women’s agency. These narratives reflect the broader struggle between self-realization and societal limitation within a patriarchal framework. The study contributes to the discourse on existential feminism in the context of Japanese literature, offering nuanced insights into embodied female resistance and the complex interplay between autonomy, identity, and systemic oppression.